Impaired spatial working memory and reduced hippocampal neuronal density in a rat model of neurocysticercosis - Baquedano, Laura E.; Bernal, Edson G.; Carrion, Daniel J.; Delgado, Ana D.; Gavidia, Cesar M.; Kirwan, Daniela E.; Gilman, Robert H.; Verastegui, Manuela R. (Frontiers in Cellular Neuroscience, 2023)
Neurocysticercosis (NCC) is the most common parasitic disease affecting the nervous system and is a leading cause of acquired epilepsy worldwide, as well as cognitive impairment, especially affecting memory. The aim of this study was to evaluate the effect of NCC on spatial working memory and its correlation with hippocampal neuronal density, in a rat model of NCC. This experimental study was conducted on female (n = 60) and male (n = 73) Holtzman rats. NCC was induced by intracranial inoc-ulation of T. solium oncospheres in 14 day-old-rats. Spatial working memory was assessed using the T-maze test at 3, 6, 9, and 12 months post-inoculation, and sensorimotor evaluation was performed at 12 months post-inoculation. Hippocampal neuronal density was evaluated by immunostaining of NeuN-positive cells of the CA1 region. Of the rats inoculated with T. solium oncospheres, 87.2 % (82/94) developed NCC. The study showed a significant decline in spatial working memory over a one-year follow-up period in rats experimentally infected with NCC. Males showed an early decline that started at 3 months, while females demonstrated it at 9 months. Additionally, a decrease in neuronal density was observed in the hippocampus of NCC-infected rats, with a more significant reduction in rats with cysts in the hippocampus than in rats with cysts in other brain areas and control rats. This rat model of NCC provides valuable support for the relationship between neurocysticercosis and spatial working memory deficits. Further investigations are required to determine the mechanisms involved in cognitive impairment and establish the basis for future treatments.